Practicality Test of Teaching Material Models for the Philosophy of Science Course in Higher Education: An Integrative-Critical Study - Jufri, Jufri; Mannahali, Misnah; Malik, Agung Rinaldy (Universitas Negeri Makassar, 2024)
Abstract. The objective of this study is to explain the practicality of the integrated-critical model for Philosophy of Science teaching materials. The model is analyzed using an integrative-critical approach. This is a developmental research study that employs both qualitative and quantitative data. The model applied is the Four-D model by Thiagarajan, which consists of four stages: Define, Design, Develop, and Disseminate. The results of the study show that the Philosophy of Science teaching materials are considered practical in terms of relevance, quality, benefits, economic efficiency, presentation strategy, coherence, logical flow of ideas, consistency, and systematic presentation. Moreover, the materials demonstrate a logical structure, balanced content, clear organization of chapters, and a variety of exercises. The practicality is also reflected in the performance outcomes of the sample, which achieved grades of A or A-, categorized as good and very good. It is hoped that future relevant studies will consider aspects such as relevance, presentation, evaluation, presentation of philosophy books, and practicality, with performance results correlating to grades of A or A-. These results are considered good and very good in the development of Philosophy of Science teaching materials in higher educationKeyword: Teaching material model, Philosophy of Science, Integrative-critical